The Study Examining the Effect of Research Activities on Economic Growth: The Case of Iran - Mehdi, Safdari (Journal of Social and Development Sciences, 2011)
The education system in every country is a regular process and each year a big part of government budget and also private investments are allocated toward this system. In addition, some of the best years of every human are spent in schools and under education. Today, the economic effects of research are accounted as very important, because the relationship between level of education and income is proved to be positive. It means that educated people, in equal situation, will earn more money. More research makes people more skilled and these skills would lead to more production and service. So, in this study we will survey the relation between educated labors and economic growth in Iran. We showed that there’s a long term relationship between these two, which is a positive and meaningful relation. In this study, we use production function (Feder, 1983), and also using auto regressive distributed lag (ARDL) co integration method, we will survey this long term relation, error correction model (ECM) and their dynamism effects. Most of past studies have used partial data (data from a certain time period); the problem with this method is that an average relationship is used, hence it won’t yield any information more than what we just need. Only the studies by Love (1987) and Wilson (1994) have used time series in surveying this relationship. But, because most of the economic time series are non stationary, there is the possibility of artificial regression. In order to avoid the consequences, unit-root tests (Phillips-Perron & Augmented Dickey-Fuller) is used.